Gender Perspectives in Literature: A Critical Inquiry into Representation, Identity, and Power - Pavan Sagar Doustan; Yashavantha T.S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Literature is a way for people to talk about ideas like gender and power. When we look at gender in literature, we can see how people think about men and women and how these thoughts change over time. This paper is about how gender is shown in books and stories. We use ideas from feminism and gender studies to see how stories show what people think about being a man or a woman. We look at books that say men should be in charge and at books that say this is not true. Some books show that gender is not one thing; it can be many things and it can change. Gender is not always the same; it can be different for people. We look at how literature shows this complexity of gender. Gender plays a significant role in shaping literary meaning and helps readers understand social inequalities and power relations. A gender-sensitive reading of literature reveals how language and narrative structures affect men and women differently. Literature not only reflects existing social norms but also contributes to changing the way people think about gender. By applying gender perspectives, scholars can offer more inclusive interpretations and give voice to women and marginalized identities. The paper emphasizes that examining gender in literature remains essential for understanding both literary texts and the changing social world.
Keywords: Gender; Literature; Feminism; Representation; Identity